Assessment of phsychological well-being and prevalence of depressive symptoms amoung young adults with type-1 diabetes mellitus - Jacob, Anu Anna; Deodhar, Divya (International Journal of Research in Medical Sciences, 2017)
Background: Depression in adolescents and young adults with type-1 diabetes mellitus has been associated with poor glycemic control and recurrent hospitalizations. The World Health Organization-Five Well- being index (WHO-5) is a simple, short and positively worded screening method to assess the level of emotional well-being and has been validated for use in adolescents with type-1 diabetes mellitus. Aims and objectives to assess the psychological well-being in adolescents and young adults with type-1 diabetes mellitus using the WHO-5 well-being index. To estimate the prevalence of symptoms of depression in type-1 diabetes mellitus using the major (ICD-10) depression inventory (MDI-ICD-10) of the psychiatric research unit. Methods: Study was a prospective study. Cases were patients with type-1 diabetes mellitus who attended the “Juvenile Diabetic Club” in CMC Ludhiana consisting of children and adolescents. Controls were healthy age matched adolescents within the family of the patients. Informed consent was taken, and they were asked to fill up the structured WHO-5 Well-being index (version 1998) questionnaire and the WHO-Major (ICD-10) Depression Inventory (MDI-ICD-10) questionnaire. Results: 36 patients were chosen for the study. There were 20 boys and 16 girls. 12 (33.3%) patients (diabetic group) had scores indicating poor well- being. P value is 0.0455, statistically significant. Among the healthy control (non- diabetic group), all of them had a scores suggesting good well- being. Conclusions: 33% of the diabetic children are depressed compared to the non-diabetic candidates in whom none are depressed.